2009
DOI: 10.1158/1055-9965.epi-08-0634
|View full text |Cite
|
Sign up to set email alerts
|

Vacations to Waterside Locations Result in Nevus Development in Colorado Children

Abstract: Nevi are a main risk factor for malignant melanoma, and most nevi develop in childhood. This study examined the relationship between vacations and nevi in 681 White children born in 1998 who were lifetime residents of Colorado. Vacation histories were assessed through telephone interviews of parents, whereas nevus and phenotypic characteristics were assessed through skin exams at age 7. Multiple linear and logistic regression were used to assess the influence of vacations on counts of nevi <2 mm in size and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
1
27
2
Order By: Relevance
“…It is also possible that intermittent intense UV exposure (rather than routine daily exposure) is required for nevus development, as has been suggested by Autier and colleagues 48. Numerous studies have noted a relationship between vacation sun exposure and nevus development, including an analysis of our full cohort at age 6 years,1416,4749 but such a relationship was not detected in this subgroup of light-skinned 8-year-olds. Likewise, sunburns were found to be related to nevus development in previous studies, including our full cohort,12,13,15,16,18,23,48 but this relationship was not found in the present analysis.…”
Section: Commentcontrasting
confidence: 61%
See 3 more Smart Citations
“…It is also possible that intermittent intense UV exposure (rather than routine daily exposure) is required for nevus development, as has been suggested by Autier and colleagues 48. Numerous studies have noted a relationship between vacation sun exposure and nevus development, including an analysis of our full cohort at age 6 years,1416,4749 but such a relationship was not detected in this subgroup of light-skinned 8-year-olds. Likewise, sunburns were found to be related to nevus development in previous studies, including our full cohort,12,13,15,16,18,23,48 but this relationship was not found in the present analysis.…”
Section: Commentcontrasting
confidence: 61%
“…Vacation sun exposure, which has been reported to be related to nevus development in several previous studies, 1416,4749 was assessed in annual interviews (2004–2006) by inquiring about any vacations to sunny locations, including the location, season, and length of trip (in days). Using methods established previously in this cohort,47 vacation locations were classified as waterside if they had a body of water and were known to be associated with recreational activities that would lead the participant to get significant sun exposure (eg, surfing, water skiing, boating).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer parents, however, are probably aware of the direct relationship between vacation sun exposure and nevi development. 4 An obvious recommendation that emerges from both facts would be the avoidance of intermittent intense UV exposure during beach or ski vacations.…”
mentioning
confidence: 99%